Rancang Bangun Sistem Sorting Barang Menggunakan 3D Simulator Factory IO Berbasis Outseal PLC - Tugino,; Mohammad Arsyad,; Septi Savitri, (ReTII, 2021)
The sorting system is one of the management systems in the selection of goods in the industry, both in terms of color, shape or size. One of the uses of PLC in industry is as a control in the process of sorting the goods. Prototype of goods sorting system based on color and size using 3D simulator factory IO based on outseal PLC using Arduino Uno and Advantech USB 4750 microcontrollers as control interfaces in factory IO applications, vision sensors as color detectors on goods, diffuse sensors as detectors on goods, conveyor as carriers, and turntables are used to sort pallets. There are 2 colors, namely blue and green that can be detected by the vision sensor where the green and blue colors will be sorted by the truntable roll. Based on the results of the tests that have been carried out, the test results of each component consisting of a vision sensor, diffuse sensor and turntable obtained results that are in accordance with the function of each component working properly and properly. The sorting system can detect goods based on color carried by the conveyor and then sorted and then goods based on color will be moved to a predetermined place